2018
DOI: 10.3897/mbmg.2.26664
|View full text |Cite
|
Sign up to set email alerts
|

Choice of DNA extraction method affects DNA metabarcoding of unsorted invertebrate bulk samples

Abstract: Characterisation of freshwater benthic biodiversity using DNA metabarcoding may allow more cost-effective environmental assessments than the current morphological-based assessment methods. DNA metabarcoding methods where sorting or pre-sorting of samples are avoided altogether are especially interesting, since the time between sampling and taxonomic identification is reduced. Due to the presence of non-target material like plants and sediments in crude samples, DNA extraction protocols become important for max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 58 publications
1
57
0
1
Order By: Relevance
“…As previously described for other types of samples (Deiner, Walser, Mächler, & Altermatt, 2015;Hermans, Buckley, & Lear, 2018;Majaneva, Diserud, Eagle, Hajibabaei, & Ekrem, 2018), the DNA extraction method was one of the main technical factors affecting metabarcoding community estimates from preservative ethanol. Overall, our results showed that column-based DNA extraction methods (TISSUE and SOIL) tended to have lower performance compared to the magnetic-based method (BEAD).…”
Section: Discussionmentioning
confidence: 99%
“…As previously described for other types of samples (Deiner, Walser, Mächler, & Altermatt, 2015;Hermans, Buckley, & Lear, 2018;Majaneva, Diserud, Eagle, Hajibabaei, & Ekrem, 2018), the DNA extraction method was one of the main technical factors affecting metabarcoding community estimates from preservative ethanol. Overall, our results showed that column-based DNA extraction methods (TISSUE and SOIL) tended to have lower performance compared to the magnetic-based method (BEAD).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA extraction method itself may affect the quantity and quality of the extracted DNA (Jedlicka, Sharma, & Almeida, ; Majaneva, Diserud, Eagle, Hajibabaei, & Ekrem, ; Oehm et al, ), with obvious downstream consequences. DNA extraction is especially important when targeting metazoans, compared to prokaryotes and micro‐eukaryotes (Dopheide et al, ).…”
Section: Factors Distorting Diet Assessmentsmentioning
confidence: 99%
“…The PCR and bioinformatic processing were conducted as described in Majaneva, Diserud, Eagle, Hajibabaei, and Ekrem (2018).…”
Section: Biological Samplingmentioning
confidence: 99%